Trade Barriers and Food Security: A Systematic Review of Import Tariff Effects in Developing Countries - Muchamad Bachtiar; Fithriyyah Shalihati; Asaduddin Abdullah (Jurnal Manajemen dan Agribisnis, 2025)
Background: Import tariffs are widely used in developing countries to manage food systems; however, their effects on the core pillars of food security under real-world shocks and institutional constraints remain debated.Purpose: To evaluate how higher versus lower (including zero) import tariffs on major foods influence food availability, access, and stability, and to draw implications for diet quality (utilization).Design/methodology/approach: A PRISMA-guided systematic literature review of Scopus-indexed, English-language journal articles (2020–2024). Twenty-five studies that met the predefined quality and relevance criteria were synthesized using a theory-driven narrative approach that describes how tariff settings shape trade and price channels, and, in turn, food security outcomes. Export restrictions are treated as exogenous stability shocks.Findings/Results: Lower tariffs generally expand market-level availability, reduce consumer prices, and dampen routine domestic volatility through import diversification. Benefits are uneven without producer upgrading and fragile during global shocks. Utilization improves when barriers to nutrient-dense foods are removed; however, openness can accelerate ultra-processed food penetration without strong nutrition governance. The effects are conditioned by logistics performance, domestic competition and pass-through, governance quality, policy space, and commodity mix.Conclusion: The most food-secure configuration is calibrated openness: liberalize where social welfare rises, pair reforms with farmer adjustment and productivity support, strengthen logistics and competition, preserve nutrition policy space, and operate a rules-based stability architecture.Originality/value (State of the art): Provides an up-to-date, developing-country synthesis that centers import tariffs, integrates utilization and governance into the trade–food security nexus, and translates evidence into operational policy guidance. Keywords: developing countries, food security, import tariffs, nutrition, trade liberalization.